2011
DOI: 10.1007/s10900-011-9367-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Mental Health Care at a Student-Run Clinic: Care for the Uninsured Exceeds that of Publicly and Privately Insured Populations

Abstract: Diagnosing and treating depression in a primary care practice is an important, yet difficult task, especially for safety-net practices serving the uninsured. In the United States healthcare system, there is a mismatch between the need for mental health care and access to services. This disparity is most striking among the uninsured. Mental health disorders are more prevalent among the uninsured, and even when diagnosed with mental illness, they are less likely to obtain necessary treatment than insured patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 27 publications
4
42
0
Order By: Relevance
“…Studies have consistently found that, compared to usual care, patients utilizing SRCs incur equal or superior outcomes (Liberman et al, 2011). The East Harlem Health Outreach Partnership (EHHOP), a student-run clinic in New York City at Mount Sinai School of Medicine, compared the mental health outcomes of their patients to those of publicly and privately insured patients in New York State (Liberman et al, 2011).…”
Section: Uses Of Student-run Clinicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have consistently found that, compared to usual care, patients utilizing SRCs incur equal or superior outcomes (Liberman et al, 2011). The East Harlem Health Outreach Partnership (EHHOP), a student-run clinic in New York City at Mount Sinai School of Medicine, compared the mental health outcomes of their patients to those of publicly and privately insured patients in New York State (Liberman et al, 2011).…”
Section: Uses Of Student-run Clinicsmentioning
confidence: 99%
“…Studies have consistently found that, compared to usual care, patients utilizing SRCs incur equal or superior outcomes (Liberman et al, 2011). The East Harlem Health Outreach Partnership (EHHOP), a student-run clinic in New York City at Mount Sinai School of Medicine, compared the mental health outcomes of their patients to those of publicly and privately insured patients in New York State (Liberman et al, 2011). They found that more EEHOP patients experienced an appropriate number of physician contacts after being diagnosed with depression, and likewise more patients received superior pharmacologic treatments (Liberman et al, 2011).…”
Section: Uses Of Student-run Clinicsmentioning
confidence: 99%
See 2 more Smart Citations
“…It also discusses models for student-run health care delivery (Der et al 2001;Bennard et al 2004;Beck 2005;Moskowitz et al 2006;Niescierenko et al 2006;Simpson & Long 2007;Rosenbaum et al 2008;Batra et al 2009;Dvoracek et al 2010;Strowd et al 2011), the ethics of SRCs (Buchanan & Witlen 2006), and patient demographics, satisfaction, and outcome data (Cadzow et al 2007;Ryskina et al 2009;Ellett et al 2010;Liberman et al 2011;Zucker et al 2011). We could identify no studies that describe SRCs as a place where medical students can learn how to teach.…”
Section: Practice Pointsmentioning
confidence: 99%